2013
DOI: 10.1590/s0104-11692013000700033
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of educational programs on reducing the burden of caregivers of elderly individuals with dementia: a systematic review

Abstract: Objective: This study's objective was to analyze the effectiveness of educational and support programs for caregivers on reducing their burden. Method: The method used was a systematic review. The following were searched; MEDLINE, LILACS, Embase, Cochrane, Web of Science, SciELO and CINAHL. Results: Seven randomized clinical studies were included. These studies compared an educational program with standard care delivery, assessing the burden of caregivers through the Zarit Burden Interview. After the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
1
27
0
5
Order By: Relevance
“…Nature of the intervention Seven reviews, all rated as moderate quality, reported on educational/ psychoeducational interventions (Elvish et al, 2013;Marim et al, 2013;Olazaran et al, 2010;Parker et al, 2008;Peacock and Forbes, 2003;Pinquart and Sorensen, 2006;Thompson et al, 2007). Four reviews used the term 'psychoeducational' to classify interventions.…”
Section: Educational and Psychoeducational Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nature of the intervention Seven reviews, all rated as moderate quality, reported on educational/ psychoeducational interventions (Elvish et al, 2013;Marim et al, 2013;Olazaran et al, 2010;Parker et al, 2008;Peacock and Forbes, 2003;Pinquart and Sorensen, 2006;Thompson et al, 2007). Four reviews used the term 'psychoeducational' to classify interventions.…”
Section: Educational and Psychoeducational Interventionsmentioning
confidence: 99%
“…Thompson et al (2007) differentiated between psychoeducational interventions that were group-based and those that were individual-based. Marim et al (2013) …”
Section: Educational and Psychoeducational Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Algunas revisiones se han centrado en valorar la eficacia de intervenciones sobre variables de resultado concretas, como la sobrecarga (Acton y Kang, 2001;Yin, Zhou y Bashford, 2002) o la sintomatología depresiva (Vázquez et al, 2014;Vázquez et al, 2015;Vázquez y Otero, 2009;Weinbrecht, Rieckmann y Renneberg, 2016). En otros casos, las revisiones se han ceñido a ciertos tipos de intervenciones, por ejemplo, programas de carácter psicoeducativo (Marim, Silva, Taminato y Barbosa, 2013) o intervenciones aplicadas en formato online (Parra-Vidales et al, 2017).…”
Section: Introductionunclassified